Usability of agricultural drought vulnerability and resilience indicators in planning strategies for small farms: a principal component approach - Sarmah, Tanaya; Balta-Ozkan, Nazmiye; Konak, Abdullah; Shrimpton, Elisabeth A.; Sass, Karina Simone; de Macedo, Marina Batalini; Mendiondo, Eduardo Mario; Nardocci, Adelaide Cassia; Huo, Da; Jacobson, Michael Gregory (Elsevier, 2025)
Water-related stresses and risks of droughts, exacerbated by climate change, have been extensively documented. These studies often rely on various indicators to monitor and forecast the impacts of droughts. However, current literature on the usability of these indicators for modelling drought risk and in decision-making processes is fragmented and lacks a clear, systematic, and methodological approach. Usability, in this context, refers to the relevance, accessibility, clarity, and practicality of indicators for guiding planning strategies. To address this knowledge gap, the Management of Disaster Risk and Societal Resilience (MADIS)1 project aims to collate and assess drought vulnerability and resilience indicators from existing literature to support decision-makers in improving policies related to agricultural droughts on small farms. The MADIS project identified over 100 indicators, from which 36 were selected for further analysis. A global online survey using the Delphi technique was conducted, and the resulting data was used to perform a Principal Component Analysis (PCA). Findings revealed that these 36 indicators could be reduced and grouped up to ten principal components, each corresponding to a theme across five categories: relevancy, understanding, accessibility, objectivity, and temporal. This study, therefore, highlights the practical usability of these indicators for developing context-specific and efficient resilience strategies. Indicators related to water management were found to be crucial and applicable across all five categories, as the availability, quality, and source of water are essential for monitoring and mitigating drought hazards. Conversely, indicators related to rural development and demographics, while quantifiable and collected at different temporal scales, were deemed less understandable and accessible by experts. Grouping indicators under common themes reduces the complexity of evaluating similar indicators and aids in selecting the most relevant ones for different contexts. This approach simplifies indicator selection and enables decision-makers to formulate resilience policies more efficiently and comprehensively.
Keywords: Agricultural drought; Resilience and vulnerability indicators; Planning strategies; Principal component analysis; Small farms; Water-energy-food nexus